Myocardial infarction model induced by isoproterenol in rats and potential cardiovascular protective effect of a nattokinase-containing hard capsule - Van Anh Pham; Ha Thai Tran; Thanh Phuong Mai; Lien Huong Nguyen; Van Hong Nguyen; Thang Huu Nguyen; Son Song Bui; An Van Vu; Ha Thanh Do; Quang Vinh Trinh (Phytomedicine Plus, 2023)
Background: TD.HK01® consists of a Japanese traditional medicine: Nattokinase (derived from soybean) and three other natural components, namely dried Hirudo medicinalis, Semen Mucuna interrupta and Huperzia carinata. Objectives: TD.HK01® is potentially aimed to the preventive treatment of cardiovascular disease (CVD) in general, and myocardial infarction (MI) in particular. Methods: In this study, a non-invasive method has been used to induce MI in rats, preceded by oral administration of TD.HK01® for 30 consecutive days to determine the potential cardiovascular effect of this pretreatment. Rats were divided into four groups: normal control group, ISO-induced group (isoproterenol (ISO), 150 mg/kg, s.c.) and two groups treated by TD.HK01® in different doses (0.31 and 0.92 g/kg, orally + ISO 150 mg/kg, s.c.). Results: TD.HK01® treated groups showed significant improvement as in abnormal electrocardiography (ECG) alteration ratio, in decreased biochemical specific markers troponin T and in decreased non-specific biochemical markers (LDH and AST) between each of TD.HK01® treated groups and ISO-induced group. The effect on vascular system was also evaluated through serum eNOS quantification and a notable increase in an anti-oxidative enzyme catalase. All three groups, except the normal control one, had pathological lesions in histopathology in different levels - modest injuries in treated groups and more severe in ISO-induced group. Conclusions: It is concluded on the basis of the findings that isoproterenol induced MI in all three groups and TD.HK01® did have its potential protective effect in vivo on cardiovascular system.